A Starry Byte — proton beam measurements of single event upsets and other radiation effects in ABCStar ASIC Versions 0 and 1 for the ITk strip tracker. (1st March 2022) - Basso, M.J.; Fernández-Tejero, J.; Gallop, B.J.; Greig, G.; John, J.J.; Keener, P.T.; Krizka, K.; Leitao, P.V.; Norman, B.; Phillips, P.W.; Poley, L.; Sawyer, C.; et al.
Abstract: Single Event Effects (SEEs) — predominately bit-flips in electronics caused by particle interactions - are a major concern for ASICs operated in high radiation environments such as ABCStar ASICs, which are designed to be used in the future ATLAS ITk strip tracker. The chip design is therefore optimised to protect it from SEEs by implementing triplication techniques such as Triple Modular Redundancy (TMR). In order to verify the radiation protection mechanisms of the chip design, the cross-section for Single Event Upsets (SEUs), a particular class of SEEs, is measured by exposing the chip to high-intensity particle beams while monitoring it for observed SEUs. This study presents the setup, the performed measurements, and the results from SEU tests performed using the latest version of the ABCStar ASIC (ABCStar V1) using a 480 MeV proton beam.